Utilization of Youtube as a Da'wah Medium: A Literature Review - Soim, Muhammad Soim (Journal of Communication Studies, 2025)
This article discusses the utilization of YouTube as a medium for da'wah in the context of rapidly advancing technology and information. As a video-based platform, YouTube has great potential to spread the messages of da'wah to a broad audience. This article aims to identify the use of YouTube as a means of da'wah through a literature review approach. This research employs a descriptive literature study methodology, examining various relevant articles, books, journals, and reports that discuss the use of YouTube in the Islamic da'wah context. The results of the review show that YouTube has great potential to support the dissemination of Islamic da'wah through engaging and easily accessible video formats for a wide audience, as well as ease in producing creative and interactive da'wah content. YouTube also enables preachers to deliver daʿwah materials visually and audibly in ways that are easier to understand by diverse groups, including the younger generation. However, the challenges encountered in its use include the potential spread of inaccurate or misleading information and the need for careful selection of content that aligns with moderate Islamic values. The conclusion of this study is that YouTube is an effective medium for preaching in the modern era, but its use must be accompanied by selectivity, caution, and a deep understanding of media ethics and the principles of conveying religious messages.